Ideas, institutions, and trade the WTO and the curious role of EU farm policy in trade liberalization - Daugbjerg, Carsten; Swinbank, A. (Alan) (Oxford : Oxford University Press, 2009)
It has always proved difficult to achieve trade liberalization for agricultural products. This book shows how a new Agriculture Agreement in the WTO led to CAP reform, which in turn allowed for greater flexibility in subsequent international trade negotiations.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Agriculture and state -- European Union countries; Agriculture -- Economic aspects -- European Union countries; Free trade -- European Union countries